Deschooling for all? The thought of Ivan Illich in the era of education (and learning) for all - Jon Igelmo Zaldívar (FahrenHouse, 2015)
Shortly after its publication in 1971, Ivan Illich's Deschooling Society made a significant impact on reports written at the most influential levels of international institutions, such as Edgar Faure's report for UNSECO, titled Learning to Be: The World of Education Today and Tomorrow (1972). However, Deschooling Society is but one of many aspects in the overall set of criticisms Illich constructed regarding education and its institutions throughout his entire career. With this matter in mind, this article presents a study on the usefulness of Illich's thoughts on education and its institutions in the debate on the «post-2015 agenda» being promoted by organisations such as UNESCO and the World Bank. The aim is to reclaim this author's works as key referents in the questioning of the theoretical grounds predominating many international development policies that advocate «Education for All» and «Learning for All» in the 21st century. How to reference this article Igelmo Zaldívar, J. (2015). Deschooling for all? The thought of Ivan Illich in the era of education (and learning) for all. Foro de Educación, 13(18), pp. 93-109. doi: http://dx.doi.org/10.14516/fde.2015.013.018.005